Domesticating the African Charter on Human and Peoples’ Rights in Ghana: threat or promise to sexual minority rights? (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:For a long time, the denial in Africa of sexual minority rights on cultural and religious grounds was firmly rooted and unchallenged. This is no longer the case. Recent scholarship has challenged the narrative that homosexuality is un-African. Gradually courts and parliaments in Africa are beginning to decriminalise colonial-era sodomy laws. In addition to progressive global and regional developments on equal legal protection for sexual minorities, it would have been difficult to imagine that the African Charter on Human and Peoples’ Rights could be used as a new pretext to deny sexual minority rights in a national constitution. Recently, however, the Constitution Review Commission of Ghana claimed that the African Charter and the Ghanaian Constitution abhor sexual minority rights. This argument ignores the pre-colonial past of many African countries, including Ghana, whose cultures embraced sexual minority rights. A consideration of the Ghanaian philosophical and theoretical thought, ‘Sankofa’, makes it imperative to turn to the past and learn from our pre-colonial cultures that embraced sexual minorities. Sankofa implores us to combine past functional cultures with current global and regional human rights law, to provide equal legal protection for every individual regardless of their sexual orientation. Therefore, domesticating the African Charter in Ghana should embrace sexual minority rights. TITRE ET RÉSUMÉ EN FRANCAIS:L’incorporation en droit interne de la Charte africaine des droits de l’homme et des peuples au Ghana: menace ou opportunités pour les droits des minorités sexuelles?RÉSUMÉ:Le déni des droits des minorités sexuelles pour des motifs culturels et religieux a longtemps été enraciné et incontesté en Afrique. Ce n’est plus le cas. Des études récentes ont remis en question l’argument selon lequel l'homosexualité n’est pas africaine. Peu à peu, les tribunaux et les parlements africains commencent à dépénaliser les lois sur la sodomie héritées de la colonisation. En plus des progrès sur le plan mondial et régional en matière d’égale protection juridique des minorités sexuelles, il aurait été difficile d’imaginer que la Charte africaine des droits de l’homme et des peuples puisse être utilisée comme un nouveau prétexte pour dénier les droits des minorités sexuelles dans une constitution nationale. Récemment, cependant, la Commission de révision constitutionnelle du Ghana a affirmé que la Charte africaine et la Constitution ghanéenne abhorraient les droits des minorités sexuelles. Cet argument ignore le passé précolonial de nombreux pays africains, dont le Ghana, où les cultures embrassaient les droits des minorités sexuelles. Un examen de la pensée philosophique et théorique ghanéenne, «Sankofa», impose de se tourner vers le passé et d'apprendre de nos cultures précoloniales qui incluaient les minorités sexuelles. Sankofa appelle à combiner les cultures fonctionnelles du passé avec le droit universel et régional actuel des droits de l'homme, afin de fournir une protection juridique égale à chaque individu quelle que soit son orientation sexuelle. Par conséquent, l’incorporation en droit interne de la Charte africaine au Ghana devrait inclure les droits des minorités sexuelles.
Keywords: African Charter on Human and Peoples’ Rights; sexual minority rights; sexual orientation; Ghana; sodomy laws